See Change: Overcoming Anti-Black Racism in Health Systems - Eisape, Adedoyin; Nogueira, André (Frontiers in Public Health, 2022)
Anti-Black racism embedded in contemporary health systems harms Black and Indigenous People of Color (BIPoC) in concert with various diseases. Seemingly unrelated at first, the COVID-19 pandemic is a recent example that reveals how the combined manifestations of anti-Black racism in disease governance, course, and burden exacerbate the historic and still present subjugation of Black people. Thus, such conditions highlight a biosocial network that intricately propagates and consolidates systems of oppression since the birth of the United States of America. In this article, we show how anti-Black racism in conjunction with past and ongoing epidemics exemplify intertwined conditions embodying and perpetuating racial inequities in the North American country. Through schematic visualizations and techniques of progressive disclosure, we situate disease governance, course, and burden as action spaces within a design model that alternates views of organizational strategies, operations, offerings, and people's experiences, supporting an action-oriented discussion in each of these spaces. We utilize insights from this analysis to recommend that public health moves forward, considering more holistic, solution-oriented questions that embrace systemic complexity and people-centered perspectives when seeking to improve health outcomes for all.